The concept of “Work-Life-Blending”: a systematic review - Steffens, Katharina; Sutter, Christine; Sülzenbrück, Sandra (Frontiers in Psychology, 2023)
Work-Life Blending refers to the permeability and dissolution of boundaries between work and personal life, bringing these domains closer together. However, a comprehensive, holistic definition or conceptualisation of Work-Life-Blending is currently lacking. This research aims to address this gap by conducting a systematic literature review to define and clarify the concept. The primary objective is to identify the key factors and dimensions of Work-Life-Blending by reviewing the current state of research, and by offering a clear and precise conceptual framework to guide further research in developing measurable and concrete concepts. We conducted a systematic review following the PRISMA guidelines to achieve this, drawing on keyword-based searches. We searched for English or German manuscripts in the electronic databases Business Source Premier and PsycARTICLES, using keywords such as “blending,” “blurring,” “fusion,” “Entgrenzung,” “Verschmelzung,” “Vermischung,” “boundary,” “border,” or “demarcation” in combination with “work” and “life.” From 1,400 screened references between 2000 and 2023, we identified 302 eligible articles. After applying exclusion criteria, 51 records were retained. Employing a holistic approach, we developed a coding scheme to analyse the articles focusing on antecedents, processes, and outcomes of Work-Life-Blending. Articles were prioritized based on their impact, relevance, and data content. Our analysis revealed a diverse field, and we adopted Clark’s central concepts (2000) to categorize Work-Life Blending into four key areas: Domains, Borders, Individual, and Interindividual. Structural analysis allowed us to gain deeper insights into the multifaceted nature of the research field. Diversification was evident in studies exploring various aspects, such as the combination of dimensions (e.g., organizational and individual factors), correlations between factors (e.g., working conditions), and the introduction of new constructs (e.g., motivational processes). Our research addresses a significant knowledge gap in the field of Work-Life-Blending, making valuable contributions to the existing body of knowledge. By examining key categories and proposing an extended definition, this study provides a robust foundation for further investigations. As a result, we established a classification of the determinants. Given the high degree of diversification, we offer a comprehensive framework for future research, contributing to a deeper understanding of Work-Life Blending.